Analisis Pengaruh Faktor Eksternal dan Internal Terhadap Tingkat Permintaan Sukuk Ritel SR008 - Cupian Anzal; Muhammad Ikhwan Al Ayyubi; Alfiah Hasanah (Al-Tijary, 2021)
Sukuk Retail SR008 was issued in 2016 as one of instrument to finance government deficit in spending . Sukuk Retail SR008 reported to have the largest number of investors and total issuance in the history of retail sukuk in Indonesia. This study investigates the effect of internal and external variables on the trading volume of retail sukuk SR008 in the short and long term. Using a montly data from June 2016 to February 2019 and use the Vector Error Correction Model (VECM), the independent variables used in this study are, retail sukuk SR008 price and yield, ORI013 retail bond price, mudhorabah profit sharing for one month, and GDP level. The results show that price sukuk retail SR008, yield sukuk retail SR008 and PDB have a positive and significant effect on the trading volume of retail sukuk SR008 in the longrun however variable share rate of mudhorabah one-month and price bond retail ORI013 have negative effect . In the short run, all independent variables have no significant effect on the retail sukuk SR008 trading volume.